Identificación del oídio causado por Erysiphe trifoliorum (Wallr.) U. Braun en Melilotus officinalis - Rugolo, Maximiliano (2016)
High incidence of the powdery mildew Erysiphe trifoliorum was diagnosed on Melilotus officinalis in Buenos Aires. Conidial germination assays were conducted in order to identify the pathogen to the species level. Images of the conidia, germination pattern, and conidiogenous cells are provided.